The sea-wolf - London, Jack, 1876-1916 (Modern Library classics., 2000)
A thrilling epic of a sea voyage and a complex novel of ideas. The Sea Wolf is a standard-bearer of its genre. The vivid story of a gentleman scholar's rescue and subsequent ordeal at the hands of a hunting schooner's brutal captain and devious crew. It remains one of Jack London's finest achievements.